ANALISIS PERSEPSI MASYARAKAT TERHADAP PROGRAM KARTU PRAKERJA DI MASA PANDEMI COVID-19 DITINJAU DARI MAQASHID SYARIAH (STUDI KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR). - Nia Oktaviani; Rully Trihantana; Ermi Suryani (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
In 2020 the unemployment rate in Indonesia will increase due to the Covid-19 pandemic. Many people are affected by layoffs (PHK), besides that there are also many unemployed from the new workforce. The government is trying to overcome this situation with a pre-employment card program during the Covid-19 pandemic. Of course, there are various kinds of perceptions among the public about the pre-employment card program. Therefore, this study aims to analyze people's perceptions (by taking the example in Cibungbulang District, Bogor Regency) towards the pre-employment card program. This study uses quantitative research methods. The results of this study indicate that the public's perception of the pre-employment card program during the Covid-19 pandemic which is seen from the factors of knowledge, profession and place of residence together has a positive influence. According to the maqashid sharia analysis, this indicates that the pre-employment card program is considered to be able to bring benefits to the community during the Covid-19 pandemic.